Celina Lucero: capstone - Lucero, Celina, artist and filmmaker (Colorado State University. Libraries, 2017)
The artist's statement: My works are inspired by the amazing creations that inhabit the entertainment industry, particularly those within the animation and videogame industry. My childhood memories are filled with fantastical scenes from Disney movies, Saturday morning cartoons, and many evenings spent playing games with my brother. There have been many worlds that I have seen and many that I have yet to see and nothing gives me greater joy than experiencing these worlds. I love the power these creations can have for its audiences when done well. Though they do not resonate well with everyone and they are not perfect, they still allow people to experience worlds other than our own while still being able to gain new ideas that can be translated into our own. Good morals can be learned and new perspectives can be opened up. The viewer can connect with characters and these fictitious characters can seem more real than the people shown to us in ads, reality TV, and magazines. I seek to tap into this power and create content that will hopefully bring joy to people so that they have something to connect to, something that can make them smile, and simply add more positivity to a world that already seems to be plenty filled with negativity and is obsessed with showing negative content.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, images of works and videos.
Videos have no spoken word.
Keywords: electronic art